Analysis of noun (direct object) collocations with the high-frequency verb DO by Spanish students in an online learner corpus - López Pérez, Sidoní; Benali Taouis, Hanane (Complutense Journal of English Studies, 2019)
This paper analyzes noun (direct object) collocations with the high-frequency verb do by Spanish university students in a computerized learner corpus that includes 155 participants and a total of 246 writing samples. The corpus includes the students’ spontaneous written contributions to a compulsory online forum from the nonlinguistic subject, ICT Tools Applied to the Learning of English, included in the curriculum of the Degree in Early Childhood Education at Universidad Internacional de La Rioja (UNIR), from 2014-2015 to 2015-2016. The analysis reveals that these learners produce collocation errors with the high-frequency verb do in two different cases: 1) when they use do instead of make; and, 2) when they make use of do as an alternative to other verbs. Results show different underlying factors which are clearly interrelated. First, the students have problems to differentiate between do and make. Second, they make use of do with delexical constructions that require make and with causative make structures. Third, they make use of patterns from their mother tongue which are not always accurate in English. Finally, the students show low collocational awareness and competence. All these aspects suggest pedagogical implications for the teaching and learning of collocations with do which are also included in the paper.